2012
DOI: 10.1007/s00701-012-1297-1
|View full text |Cite
|
Sign up to set email alerts
|

iNOS-mediated secondary inflammatory response differs between rat strains following experimental brain contusion

Abstract: Two inbred rat strains with genetically determined differences in susceptibility to develop autoimmune disease displayed different levels of the inflammatory and anti-inflammatory mediators iNOS and MnSOD, indicating genetic regulation. Interestingly, the increased levels of iNOS did not lead to elevated expression of the neuronal cell-death marker fluoro-jade. The increased iNOS expression was correlated with increased expression of superoxide scavenger MnSOD. Excessive peroxynitrite formation was probably pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…iNOS mRNA and protein increased on the ipsilateral side at 24 h with no expression on the contralateral side, correlating to our earlier findings of mild to moderate TBI [10,8]. iNOS is upregulated by transcription factors NFkB, STAT-1, IRF-1 and AP-1 and is a main producer of NO following TBI, causing oxidative stress [24,28].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…iNOS mRNA and protein increased on the ipsilateral side at 24 h with no expression on the contralateral side, correlating to our earlier findings of mild to moderate TBI [10,8]. iNOS is upregulated by transcription factors NFkB, STAT-1, IRF-1 and AP-1 and is a main producer of NO following TBI, causing oxidative stress [24,28].…”
Section: Discussionsupporting
confidence: 85%
“…Due to the negative nature of the contralateral side, for illustrative purposes this is shown only in males putative differences in inflammatory activity between genders, which may have been undetected in other models of TBI. Comparisons were made between the injured and intact hemispheres, in line with our studies of identical or comparable inflammatory markers [10,31]. Sham-treated animals were excluded as they would be irrelevant to the specific hypothesis and weaken the statistical power in the comparison of groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantification of Fluoro-Jade, manganese superoxide dismutase (MnSOD), Ox-42 (CD11b), 3-nitrotyrosine (3-NT) and iNOS was done by group blinded manual cell counting in eight sections per animal and marker in the ROI at 20-40Â magnification, according to our earlier study, [29] using a Nikon Eclipse E600 (Nikon, Chiyoda, Tokyo, Japan). Filters used were for Cy3 G-1B (excitation/emission [ex/em] 541-551/590 nm), Alexa 488 and Fluoro-Jade filter fluorescein isothiocyanate (FITC; ex/em 465-495/515-555 nm), DAPI filter (ex/em 340-380/435-485).…”
Section: Methodsmentioning
confidence: 99%
“…These three isoforms of the enzyme nitric oxide synthase (NOS) that are present in the central nervous system (CNS) can produce nitric oxide (NO). eNOS is expressed in the vascular endothelium and choroid plexus; neuronal NOS is mainly expressed in neuronal cell bodies, especially in the cortex, hippocampus, hypothalamus, olfactory bulb, claustrum, amygdala, and thalamus; and inducible NOS is expressed in macrophages, glial cells, infiltrating neutrophils, and, to some extent, neurons [1]. It has also been reported that eNOS can be found in a subset of neurons and astrocytes and that nNOS can be found at low levels in astrocytes [2].…”
Section: Introductionmentioning
confidence: 99%